2021
DOI: 10.1182/blood.2020009729
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive transcriptome signature of murine hematopoietic stem cell aging

Abstract: We surveyed 16 published and unpublished data sets to determine whether a consistent pattern of transcriptional deregulation in aging murine hematopoietic stem cells (HSC) exists. Despite substantial heterogeneity between individual studies, we uncovered a core and robust HSC aging signature. We detected increased transcriptional activation in aged HSCs, further confirmed by chromatin accessibility analysis. Unexpectedly, using two independent computational approaches, we established that deregulated aging gen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 52 publications
3
47
0
Order By: Relevance
“…On the other hand, Figueroa and colleagues have demonstrated that the signal intensity of H3K27me3 peaks decreases with age in a human HSC-enriched population [91], highlighting the complexity of age-related changes in PRC2 activity. The expression of Ezh1 may increase with age [90,92], albeit this observation appears not always to be reproduced [93]. Although the function of EZH1 and EZH2 seems largely overlapping, EZH1 has non-redundant, ontogeny-specific, and dose-dependent roles, such as inhibition of HSC emergence before definitive hematopoiesis via repression of HSC signature genes, and the prevention of adult HSC depletion by Cdkn2a repression [92,94].…”
Section: Epigenetic Memorymentioning
confidence: 99%
“…On the other hand, Figueroa and colleagues have demonstrated that the signal intensity of H3K27me3 peaks decreases with age in a human HSC-enriched population [91], highlighting the complexity of age-related changes in PRC2 activity. The expression of Ezh1 may increase with age [90,92], albeit this observation appears not always to be reproduced [93]. Although the function of EZH1 and EZH2 seems largely overlapping, EZH1 has non-redundant, ontogeny-specific, and dose-dependent roles, such as inhibition of HSC emergence before definitive hematopoiesis via repression of HSC signature genes, and the prevention of adult HSC depletion by Cdkn2a repression [92,94].…”
Section: Epigenetic Memorymentioning
confidence: 99%
“…9. GSEA Using "Aging Signature Gene Sets" as Reference Svendsen et al surveyed 16 published and unpublished transcriptome datasets from comparisons of aged and young murine HSPC [20]. They were able to identify a list of 220 genes that were consistently deregulated in aging murine HSPC.…”
Section: Gene Set Enrichment Analysis (Gsea)mentioning
confidence: 99%
“…Present evidence indicates that aging involves a gradual, heterogeneous deficiency in the structure and function of a subpopulation of HSPC that have become senescent [ 19 ]. With the advances made in multi-omics analysis, HSPC from young mice have been compared with aged mice and the differential gene expression profiles of aged HSPC characterized [ 20 ]. Transcriptomics studies have provided a blueprint of the underlying molecular mechanisms and indicated that genes associated with DNA damage and repair, myeloid lineage specification, as well as with myeloid malignancies were upregulated in old HSPC [ 7 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptome from aged HSCs (from mice maintained in pathogen-free conditions) is enriched in genes associated with inflammation, stress response and protein aggregation while chromatin remodeling and genome integrity associated genes were downregulated suggesting an epigenetic resetting with age. Of particular interest is upregulation of P-selectin and NFκβ activation, which is a master regulator of inflammatory gene expression ( Chambers et al, 2007 ; Svendsen et al, 2021 ). Transplantation of P-Selectin high HSCs from aged mice into irradiated young niches resulted in skewed myeloid differentiation from these cells.…”
Section: Inflamm-aging In Stem Cell Decisions and Regeneration In Tis...mentioning
confidence: 99%
“…Transplantation of P-Selectin high HSCs from aged mice into irradiated young niches resulted in skewed myeloid differentiation from these cells. Further P-selectin high aged HSCs exhibited higher cycling ( Svendsen et al, 2021 ). However, a direct role of P-selectin signaling in the aging phenotype has not been established.…”
Section: Inflamm-aging In Stem Cell Decisions and Regeneration In Tis...mentioning
confidence: 99%